Home-based palliative care: A systematic literature review of the self-reported unmet needs of patients and carers. (May 2014) - Ventura, Adriana D; Burney, Susan; Brooker, Joanne; Fletcher, Jane; Ricciardelli, Lina
Background: There have been many studies on the unmet needs of palliative care patients and carers from the perspective of bereaved caregivers. However, the unmet needs of palliative care patients and carers from the perspective of current patients and their carers have received little research attention. Aim: As home-based services have become one of the main delivery models of palliative care, the aim of this review was to describe, evaluate and summarise the literature on the unmet needs of palliative home care patients and carers. Design: The systematic review of qualitative and quantitative studies was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data sources: PubMed, CINAHL, Embase, MEDLINE, PsycINFO, AMED and CareSearch were searched to find empirical studies on the self-reported unmet needs of palliative home care patients and carers. Results: Nine qualitative studies, three quantitative studies and three mixed-design studies were identified. The most frequently reported unmet need was effective communication with health-care professionals, the lack of which negatively impacted on the care received by patients and carers. Physical care needs were met, which indicates that the examined palliative home care services were delivering satisfactory care in this domain, but lacking in other areas. Conclusions: The focus therefore should be on improving other aspects of patient care, including communication by health professionals to prevent or reduce suffering in areas such as psychosocial domains. Valid and reliable quantitative measures of unmet needs in palliative care are needed to examine this area more rigorously.